Effect of Alpha-Tocopherol Supplementation in TCM199 Medium on In Vitro Maturation and Cleavage of Buffalo Oocytes - Lakshmi, Vijaya; Kulkarni, Shrikant; Satisha, KB; Yatish, Hm; Girish, MH; Kumar, GS Naveen; Bijurkar, RG; Das, Amba; Yogesh; karikesh, SM (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
An experiment was conducted to assess the effect of supplementing α-tocopherol at two different concentrations to the in vitro maturation (IVM) medium (TCM 199 culture medium) on in vitro maturation and cleavage of buffalo oocytes. Ovaries were collected from local slaughter house. Oocytes were collected by aspiration method and were matured in IVM medium (T0, control), IVM medium supplemented with α-tocopherol @ 10 µg/ml (T1) and IVM medium supplemented with α-tocopherol @ 20 µg/ml (T2). The mean cytoplasmic maturation rate was 82.39 ± 0.81, 88.81 ± 1.08, 81.67 ± 1.82 % and nuclear maturation rate was 62.50 ± 8.33, 87.50 ± 5.59, 66.66 ± 7.68 % in T0, T1 and T2 groups, respectively. The fertilized oocytes reaching 2-cell and 4-cell stages of cleavage for T0, T1 and T2 groups were 14.92 ± 1.52, 32.39 ± 1.01 and 16.39 ± 1.25 %, respectively. Significantly (p <0.05) higher level of cytoplasmic maturation rate, nuclear maturation rate and cleavage rate was observed in IVM medium supplemented with α-tocopherol @10 µg/ml than other two groups.